2017
DOI: 10.1097/sga.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Hepatitis B Antiviral Therapy

Abstract: Hepatitis B virus (HBV) antiviral therapies potentially suppress HBV viral load to an undetectable level reducing the risk of progressive liver disease and the development of HBV-related hepatocellular carcinoma. Adherence to antiviral therapies is imperative to achieve and maintain viral suppression. To date, there has been limited research on adherence to HBV therapies. Our study aimed to explore factors influencing adherence to antiviral therapy. A total of 29 participants consented to in-depth qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…From an initial screen of 878 titles, 30 studies providing data for 23,823 patients met our eligibility criteria and were taken through for review (Fig. ) . The majority (23 studies, 17,057 patients) were from high‐income settings, mainly the United States (seven studies), Australia (four studies), and France (three studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an initial screen of 878 titles, 30 studies providing data for 23,823 patients met our eligibility criteria and were taken through for review (Fig. ) . The majority (23 studies, 17,057 patients) were from high‐income settings, mainly the United States (seven studies), Australia (four studies), and France (three studies).…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to adherence were reported by seven studies . Among patients with suboptimal adherence, the most commonly reported barriers to adherence were forgetting (three studies, 81.1%; 95% CI, 68.7%‐93.5%), limited understanding of the importance of adherence (two studies, 32.3%; 95% CI, 17.2%‐47.4%), and change to daily routine (two studies, 27.4%; 95% CI, 4.7%‐50.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed in our earlier qualitative study, non-adherent participants who commenced HBV treatment at a younger age (< 45 years) described a period of transition and adjustment to taking medicine daily. This group of patients described the importance of establishing a routine when treatment commenced [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not formally measured health literacy in HBV-affected populations undergoing treatment. Language discordance [14] and ineffective communication between patients and clinicians [19] have been reported to influence adherent behaviour without measuring health literacy as a potential factor contributing to misinterpretation of key health messages. Considering that more than half of the current study population reported less than adequate health literacy and that the HBV-affected population in Australia is composed primarily of migrants from non-English-speaking HBV-endemic countries [41], it is essential that health care providers are universally responsive to the individual health literacy needs of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation